2006
DOI: 10.1073/pnas.0510700103
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genomics provides evidence for close evolutionary relationships between the urotensin II and somatostatin gene families

Abstract: Although urotensin II (UII) and somatostatin 1 (SS1) exhibit some structural similarities, their precursors do not show any appreciable sequence identity and, thus, it is widely accepted that the UII and SS1 genes do not derive from a common ancestral gene. The recent characterization of novel isoforms of these two peptides, namely urotensin II-related peptide (URP) and somatostatin 2 (SS2)͞ cortistatin (CST), provides new opportunity to revisit the phylogenetic relationships of UII and SS1 using a comparative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
52
0
6

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(59 citation statements)
references
References 65 publications
(68 reference statements)
1
52
0
6
Order By: Relevance
“…In mammals, SS2 was originally called as cortistatin (CST). Because SS2s and CSTs possess a proline residue at position 2, all the [Pro 2 ] somatostatin variants, that are orthologous to cortistatins (Tostivint et al, 2006), have been now termed SS2 (Tostivint et al, 2008). Moreover, two additional somatostatin genes SS3 and SS4 have been identified from teleost fish.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In mammals, SS2 was originally called as cortistatin (CST). Because SS2s and CSTs possess a proline residue at position 2, all the [Pro 2 ] somatostatin variants, that are orthologous to cortistatins (Tostivint et al, 2006), have been now termed SS2 (Tostivint et al, 2008). Moreover, two additional somatostatin genes SS3 and SS4 have been identified from teleost fish.…”
Section: Introductionmentioning
confidence: 99%
“…The zebrafish is now the only vertebrate in which all four SS genes have been identified. It seems that the somatostatins belong to a large polygenic family that also includes urotensin II and urotensin IIrelated peptide (Tostivint et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Although the N-terminal Alanine-Glycine sequence of Gillichthys UII was the same as for human somatostatin-14, the N-terminal sequence of human UII differed, pointing to the essential nature of the FWK sequence in the cyclic 6-membered disulphide-bonded ring for the biological activity of UII. Comparative genomic studies now indicate a common ancestral gene for UII and the somatostatin/cortistatin genes (Tostivint et al, 2006). What was not commented upon at the time is the striking structural analogy between UII and the essential six amino acid cyclic conformation of both oxytocin and vasopressin (Table 1).…”
Section: Isolating and Sequencing The Urotensins In Parallel With Crfmentioning
confidence: 99%
“…The mature form of UII has a cyclic structure formed by a disulfide bond at the C terminus, in which the '-Cys-Phe-Trp-Lys-Tyr-Cys-' sequence is fully conserved across vertebrate species, whereas the amino acid sequence at the N terminus is rather variable (Onan et al 2004, Conlon 2008, Vaudry et al 2010. Comparative genomic studies have shown that the UII and somatostatin (SS) genes derive from a common ancestral gene (Tostivint et al 2006(Tostivint et al , 2008. Both these genes share the common -Phe-Trp-Lys-sequence, which is functionally important.…”
Section: Introductionmentioning
confidence: 99%
“…UT shares high sequence identity with the SS receptors (SSTRs). Both UT and one of the SSTRs, SSTR3, are located on the same chromosome (Tostivint et al 2006(Tostivint et al , 2008. In mammals, both UII and UT are widely expressed in the CNS and various peripheral tissues (Onan et al 2004, Malagon et al 2008.…”
Section: Introductionmentioning
confidence: 99%